2018
DOI: 10.1007/s13272-018-0337-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on fixed flight-path angle descent for wide-body passenger aircraft

Abstract: This study proposes the use of fixed flight-path angle (FPA) descent as a potential alternative for eco-friendly air traffic operations. Additionally, given that the proposed descent procedure follows a fixed, assigned flight-path angle, with the aircraft continuously descending toward the runway threshold with near-idle thrust, the trajectory should be more predictable for air-traffic controllers. As such, the proposed approach is expected to contribute significantly toward decreasing the air traffic fuel con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The vertical profile for all runs is initialised at 38,000ft (FL380). From top of descent until capturing the −3.0-degree glideslope, a continuous descent approach with a fixed geometrical flight path angle of −2.2degrees (18,28) was used, as shown in Fig. 8.…”
Section: Vertical Profilementioning
confidence: 99%
“…The vertical profile for all runs is initialised at 38,000ft (FL380). From top of descent until capturing the −3.0-degree glideslope, a continuous descent approach with a fixed geometrical flight path angle of −2.2degrees (18,28) was used, as shown in Fig. 8.…”
Section: Vertical Profilementioning
confidence: 99%
“…More recently, Itoh et al (2018a) and Itoh et al (2018b) also studied the operational feasibility of CDOs from the point of view of pilots when flying fixed flight-path angle descents. Results showed that this technique improves the efficiency of the flight and, according to the pilots, operationally stable flights for B777-200 aircraft could be achieved providing the flight path angle is around 2.5 degrees.…”
Section: I22 Fixed Flight-path Angle Descentsmentioning
confidence: 99%